2013
DOI: 10.1115/1.4024736
|View full text |Cite
|
Sign up to set email alerts
|

Design and Kinematical Performance Analysis of a 3-RUS/RRR Redundantly Actuated Parallel Mechanism for Ankle Rehabilitation

Abstract: In this paper, we present the design of a novel 3-RUS/RRR redundantly actuated parallel mechanism for ankle rehabilitation based on the principle from the conceptual design. The proposed mechanism can actualize the rotational movements of the ankle in three directions while at the same time the mechanism center of rotations can match the ankle axes of rotations compared with other multi-degree-of-freedom devices, owing to the structural characteristics of the special constraint limb and platform. A new actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…PMA have intrinsic elasticity (compliance) which can be used in providing compliant actuation [41]. Several robotic orthoses powered by PMA have been developed for the gait training of neurologically impaired subjects [38,40,[42][43][44][45][46][47]. However, in most of the cases, only trajectory-tracking control has been applied to these PMA powered robotic gait training orthoses [38,48].…”
Section: Assist-as-needed Control Of An Intrinsically Compliant Robotmentioning
confidence: 99%
“…PMA have intrinsic elasticity (compliance) which can be used in providing compliant actuation [41]. Several robotic orthoses powered by PMA have been developed for the gait training of neurologically impaired subjects [38,40,[42][43][44][45][46][47]. However, in most of the cases, only trajectory-tracking control has been applied to these PMA powered robotic gait training orthoses [38,48].…”
Section: Assist-as-needed Control Of An Intrinsically Compliant Robotmentioning
confidence: 99%
“…Assume that 1 and 2 are at 30 and 60 , respectively. Repeating the process of equations (8) to (11) according to the result, the relationship of curves of and is as shown in Figure 4. In Figure 4, two loops for arm1 and arm2 are drawn, respectively.…”
Section: Kinematics Solution Forward and Inverse Kinematicsmentioning
confidence: 99%
“…In addition, as it is shown in Figure 4, the dashed line for arm1 is nearly parallel to axis which means is sensitive to . So in equation (11), choosing the independent variable from t and t should be done carefully.…”
Section: Kinematics Solution Forward and Inverse Kinematicsmentioning
confidence: 99%
“…Nowadays, it can found that parallel manipulators are related with many real world applications, e.g. multi-axis machine tools, motion simulators, picking and placing devices, micronano manipulators, cable driven robots, three-dimensional printers, to name a few of them (Carricato and Merlet 2013;Kima et al 2008;Gao et al 2010a, b;Hou et al 2009;Wang et al 2013). Although it has been claimed that parallel mechanisms/manipulators have the nature advantages of in terms of dexterity, precision, load ability and accuracy (Carricato 2013;Patchaikani et al 2012;Zhang and Gao 2012;Refaat et al 2007;Jensen et al 2006;Taghirad and Bedoustani 2011;Axinte et al 2011;Uriarte et al 2013;Liu et al 2003;Refaat et al 2007), overall performance is still the main factor that affects their development.…”
Section: Introductionmentioning
confidence: 99%